2011
DOI: 10.1097/gim.0b013e3182056133
|View full text |Cite
|
Sign up to set email alerts
|

Patient reactions to personalized medicine vignettes: An experimental design

Abstract: Purpose Translational investigation on personalized medicine is in its infancy. Exploratory studies reveal attitudinal barriers to “race-based medicine” and cautious optimism regarding genetically personalized medicine. This study describes patient responses to hypothetical conventional, race-based, or genetically personalized medicine prescriptions. Methods Three hundred eighty-seven participants (mean age = 47 years; 46% white) recruited from a Baltimore outpatient center were randomized to this vignette-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 37 publications
0
20
1
Order By: Relevance
“…Consistent with a broader range of expected risks and benefits, for some AAs, a providermanaged and -driven model for returning results may be unacceptable or less effective [Butrick et al, 2011]. AA participants shared stories about negative health care experiences that stress the importance of maintaining control over the receipt of results.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with a broader range of expected risks and benefits, for some AAs, a providermanaged and -driven model for returning results may be unacceptable or less effective [Butrick et al, 2011]. AA participants shared stories about negative health care experiences that stress the importance of maintaining control over the receipt of results.…”
Section: Discussionmentioning
confidence: 99%
“…Rahm et al examined perceptions of DTC-PGT advertising among various demographic groups and reported that individuals from minority groups may not consider genetic knowledge to be as empowering as Whites (Rahm et al 2012). One vignette-based study found that minority groups were more likely to report reluctance to adhere to medical prescriptions based on genetics compared to conventional prescriptions (Butrick et al 2011). While racial differences in knowledge/interest in genetic testing have been reported (Mai et al 2014;Pagan et al 2009 (Catz et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, health literacy needs to be increased by clear communication channels to adjust the public's expectations and information about biomarkers (including genomic assays). Besides the utility of CDx, concerns on privacy regulations and genetic discrimination that exist among the public should be reduced [3,25,61,62,63,64,65]. Within the communication to patients, the legislation for privacy concerning genomic information has to be stated clearly [2].…”
Section: Resultsmentioning
confidence: 99%